Probability

IF A A and B B are two independent events such that P ( A c B ) = 2 15 P (A^c \cap B ) =\dfrac2{15} , and P ( A B c ) = 1 6 P (A \cap B^c) = \dfrac16 , find P ( A ) P(A) and P ( B ) P(B) .

P ( A ) = 1 5 , 5 6 , P ( B ) = 4 5 , 1 6 P(A)=\frac{1}{5},\frac{5}{6}, P(B)= \frac{4}{5},\frac{1}{6} P ( A ) = 1 5 , 7 11 , P ( B ) = 4 5 , 4 11 P(A)=\frac{1}{5},\frac{7}{11}, P(B)= \frac{4}{5},\frac{4}{11} P ( A ) = 3 8 , 2 7 , P ( B ) = 5 8 , 4 7 P(A)=\frac{3}{8},\frac{2}{7}, P(B)= \frac{5}{8},\frac{4}{7} None of the above P ( A ) = 2 3 , 5 6 , P ( B ) = 1 3 , 1 6 P(A)=\frac{2}{3},\frac{5}{6}, P(B)= \frac{1}{3},\frac{1}{6}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Feb 15, 2016

Knowing that for any event X => P(X) + P(X') = 1, let us write:

P(A' and B) = P(A')P(B) = [1 - P(A)]*P(B) = P(B) - P(A)P(B) = 2/15 (i)

P(A and B') = P(A)P(B') = P(A)*[1 - P(B)] = P(A) - P(A)P(B) = 1/6 (ii).

Subtracting (i) from (ii) produces P(A) - P(B) = 1/30, or P(A) = P(B) + 1/30 (iii). Substitution of (iii) into (ii) yields:

P(A) [1 - P(B)] = 1/6 => [1/30 + P(B)][1 - P(B)] = 1/6 => 1/30 + (29/30) P(B) - P(B)^2 = 1/6 (iv). Solving the quadratic equation in (iv) for P(B) produces P(B) = 1/6, 4/5, and plugging these values into (iii) yields P(A) = 1/5, 5/6 respectively.

Hence the answer is P(A) = 1/5, 5/6 and P(B) = 1/6, 4/5.

In the "correct" answer of the problem is written P(B)=4/5, 1/6! This is not 1/6, 4/5 with which I agree. This is why I answered None etc.

Wim Kerstens - 5 years, 3 months ago

Log in to reply

I agree the answer choices are worded a little confusingly, Wim! It would've made more sense to group P(A) & P(B) as ordered-pairs instead. Kudos for still trying everything out :)

tom engelsman - 5 years, 3 months ago

If (A and B) are independent events then (A' and B) and (A and B') must be dependent events. Visualize this using Venn diagram , so the above formula used in ans is wrong rather, this formula should be used --> P(A' and B) = P(A')P(B|A') or P(A and B')=P(B)P(A'|B). Please let me know if I'm wrong.

GAURAV YADAV - 1 year, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...